Secondary batteries and electrical devices
By using lithium-containing materials with olivine structure in the positive electrode sheet of lithium-ion battery and controlling the redox reaction characteristics, the third discharge platform was introduced, which solved the problem of the battery's discharge power drop in low temperature and low SOC states, and achieved high energy Take into account both density and high discharge power.
Patent Information
- Application Number
- CN202411641275.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The discharge power of existing lithium-ion batteries decreases in low temperature and low SOC states, which cannot meet the usage requirements in certain harsh environments. At the same time, while increasing the discharge power, it is difficult to maintain or increase the energy density.
The lithium-containing material including an olivine structure is used as the positive electrode active material. By comprehensively controlling the redox reaction characteristics, the third discharge platform is introduced, and the potential difference between the second discharge platform and the third discharge platform, the third discharge platform and the following proportion of discharge capacity.
The secondary battery has a high discharge power and good energy density at low temperatures and low SOCs, which meets multiple requirements for battery performance.
Smart Images

Figure CN119153687B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, in particular to a secondary battery and an electrical device. Background Art
[0002] With the advancement of modern technology and the increase in consumer demand, the application areas of lithium-ion batteries are constantly expanding, from portable electronic devices to electric vehicles to large-scale energy storage systems. These applications not only require batteries to have higher energy density, but also place higher demands on the power output capacity of batteries.
[0003] Lithium manganese iron phosphate (LMFP) is gradually becoming a research hotspot in the field of lithium-ion batteries due to its excellent energy density and relative safety. However, although LMFP materials have good energy density, their ion diffusion rate is low, resulting in a decrease in the discharge power of the battery. Especially in low temperature environments and when the battery is in a low SOC state, the chemical reaction rate inside the battery is significantly slowed down, which seriously affects the discharge power of the battery and cannot meet the use requirements in certain harsh environments.
[0004] Lithium iron phosphate (LFP) material has good conductivity and high electron transfer rate, which enables the battery to have relatively high power output. However, the blending of LFP and LMFP inevitably leads to a decrease in battery energy density, limiting the application of batteries in scenarios that require high energy density.
[0005] Therefore, how to maximize or even improve the energy density of the battery while ensuring its low-temperature power performance has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electrical device. The positive electrode plate of the secondary battery adopts a lithium-containing material including an olivine structure as the positive electrode active material. By comprehensively controlling the redox reaction characteristics of the positive electrode active material, the secondary battery has a higher discharge power at low temperature and low SOC and a good energy density.
[0007] To achieve the above object, in a first aspect of the present invention, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium-containing material having an olivine structure;
[0008] The secondary battery is charged and discharged at 0.33C at 25°C to obtain a discharge curve; the discharge curve includes three discharge platforms with different potentials, which are sequentially recorded as the first discharge platform, the second discharge platform and the third discharge platform in descending order of potential;
[0009] The potential difference between the second discharge platform and the third discharge platform is recorded as △U, and the range of △U is 23~192mV;
[0010] The proportion of the discharge capacity at the third discharge platform and below to the total discharge capacity of the secondary battery is recorded as Q, and the range of Q is 3.5~88%.
[0011] In a second aspect of the present invention, the present invention provides a secondary battery comprising the positive electrode sheet described above.
[0012] In a third aspect of the present invention, the present invention provides an electrical device comprising the secondary battery described above.
[0013] The beneficial effects of the present invention are:
[0014] The present invention provides a secondary battery and an electric device. The positive electrode plate of the present invention uses a lithium-containing material including an olivine structure as a positive electrode active material, and by comprehensively controlling the redox reaction characteristics of the positive electrode active material, the secondary battery containing the positive electrode plate has a higher discharge power at low temperature and low SOC and good energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a discharge curve diagram of the lithium-ion battery of Example 7.
[0016] Figure 2 dQ / dV-V curve of the lithium ion battery of Example 7.
[0017] Figure 3 dV / dQ-Q curve of the lithium ion battery of Example 7. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0020] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0021] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0022] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0023] Secondary battery
[0024] An embodiment of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises a lithium-containing material having an olivine structure;
[0025] The secondary battery is charged and discharged at 25°C and 0.33C in a voltage range of 2.5-4.25V to obtain a discharge curve; the discharge curve includes three discharge platforms with different potentials, which are sequentially recorded as the first discharge platform, the second discharge platform and the third discharge platform in descending order of potential;
[0026] The potential difference between the second discharge platform and the third discharge platform is recorded as △U, and the range of △U is 23~192mV;
[0027] The proportion of the discharge capacity of the third discharge platform to the total discharge capacity of the secondary battery is recorded as Q, and the range of Q is 3.5~88%.
[0028] The present invention comprehensively controls the redox reaction characteristics of the positive electrode active material, introduces a third discharge platform, and controls the potential difference between the second discharge platform and the third discharge platform and the proportion of the discharge capacity of the third discharge platform and below, so that the secondary battery containing the positive electrode plate has higher discharge power at low temperature and low SOC and good energy density.
[0029] The relationship between the battery's output power (P), voltage (U), and current (I) is P=U×I=(U initial −U 差值 )×I, where U initial is the initial voltage, U 差值is the voltage drop. The material impedance of LMFP is very large at low temperatures. During pulse discharge, the positive electrode potential will drop rapidly. 差值 The voltage drop is very large, which leads to a rapid decrease in battery potential and poor power. Therefore, in order to increase the output power, on the one hand, the initial voltage is increased, and on the other hand, the voltage drop is reduced.
[0030] The value of △U reflects the difference between the potential of the third discharge platform and the potential of the second discharge platform (the potential of the second discharge platform - the potential of the third discharge platform = U value). The present invention has found that the size of the △U value affects the initial voltage on the one hand and the voltage drop on the other hand. The △U value should be within an appropriate range, which helps the battery to have both a higher initial voltage and a lower voltage drop. When the △U value is too large, it may be that the potential of the introduced third discharge platform is too low, and the initial discharge voltage of the secondary battery at low SOC discharge is too low; it may also be that the voltage of the second platform is too high, resulting in a large voltage drop caused by battery discharge, and the overall dynamics of the secondary battery deteriorates; both of these situations will affect the output power, resulting in a reduction in power. When the △U value is too small, that is, the second and third platforms are infinitely close, the average operating voltage of the battery decreases, resulting in a decrease in the specific energy density of the battery.
[0031] The size of the Q value reflects the capacity proportion of the third discharge platform. When the Q value is too small, the capacity proportion of the introduced third discharge platform is too low, and it cannot increase the initial voltage and thus improve the discharge power of the battery at low temperature and low SOC. When the Q value is too large, the capacity proportion of the third discharge platform is too large, which will cause the average discharge voltage of the battery to be lowered, resulting in a decrease in the overall energy density of the battery.
[0032] For lithium-containing materials with olivine structure, their element composition and element content, as well as specific material selection, may affect the △U and Q values. The present invention has found that when the range of △U is controlled to be 23~192mV and the range of Q is 3.5~88%, the secondary battery containing the positive electrode sheet can have excellent low temperature, low SOC discharge power and high energy density.
[0033] In the present invention, the values of ΔU and Q can be obtained from the dQ / dV-V and dV / dQ-Q diagrams of the secondary battery containing the positive electrode sheet. Specifically, ΔU and Q can be measured by the following method:
[0034] (1) Constant capacity: The secondary battery was allowed to stand at 25°C for 120 min, and then discharged at a constant current of 0.33C to 2.5V; after standing for 20 min, it was charged at a constant current and constant voltage of 0.33C to a cut-off voltage of 4.25V and a cut-off current of 0.05C; after standing for 20 min, it was discharged at a constant current of 0.33C to 2.5V; after the above steps were repeated once, the discharge QV data and discharge VQ data of the second cycle were obtained;
[0035] (2) Drawing a dQ / dV-V curve: Based on the above discharge QV data, 100 points are sampled at equal intervals as the initial data of Dv and Dq, and the voltage and power data of the nth data point are subtracted from the voltage and power data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dQ is divided by dV to obtain dQ / dV; dQ / dV is used as the ordinate and voltage is used as the abscissa to draw a dQ / dV-V curve;
[0036] (3) In the obtained △U:dQ / dV-V curve, in the range of 3.0~4.1V, according to the order of the horizontal axis voltage from low to high, the horizontal axis voltage U3 corresponding to the peak position of the first characteristic peak is the potential of the third discharge platform, the horizontal axis voltage U2 corresponding to the peak position of the second characteristic peak is the potential of the second discharge platform, and the horizontal axis voltage U1 corresponding to the peak position of the third characteristic peak is the potential of the first discharge platform;
[0037] U2-U3=potential difference between the second discharge platform and the third discharge platform (△U);
[0038] (4) Drawing a dV / dQ-Q curve: Based on the above discharge VQ data, 100 points are sampled at equal intervals as the initial data of Dv and Dq, and the voltage and power data of the nth data point are subtracted from the voltage and power data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dV is divided by dQ to obtain dV / dQ; dV / dQ is used as the ordinate and Q is used as the abscissa to draw a dV / dQ-Q curve;
[0039] (5) Obtaining Q: In the dV / dQ-Q curve, the maximum horizontal axis is read as the total maximum discharge capacity Q0, and the peak close to the Q0 side (right side) is defined as peak C; the horizontal axis capacity corresponding to the peak value of the total discharge capacity-peak C is the discharge capacity of the third discharge platform (denoted as Q3), and the proportion of the discharge capacity of the third discharge platform to the total discharge capacity (Q) = Q3 / Q0×100%.
[0040] Exemplarily, the range of △U can be 23mV, 25mV, 30mV, 40mV, 60mV, 80mV, 100mV, 130mV, 150mV, 160mV, 170mV, 180mV, 185mV, 190mV, 192mV, or it can be an interval range formed by any two of the above values.
[0041] Exemplarily, the range of Q can be 3.5%, 5.0%, 8.0%, 10.0%, 15.0%, 30.0%, 50.0%, 60.0%, 70.0%, 75.0%, 80.0%, 85.0%, 87.0%, 88.0%, or it can be an interval range formed by any two of the above values.
[0042] As a preferred embodiment of the present invention, the range of ΔU is 50~175mV.
[0043] As a preferred embodiment of the present invention, the range of Q is 8.0~82%.
[0044] When ΔU or Q is within the above preferred range, the energy density and low-temperature power of the secondary battery containing the positive electrode plate are relatively more balanced and better overall.
[0045] As a preferred embodiment of the present invention, the potential of the second discharge platform is 3.25-3.4 V.
[0046] As a preferred embodiment of the present invention, the potential of the third discharge platform is 3.1-3.25 V.
[0047] As a preferred embodiment of the present invention, an EIS test is performed on a secondary battery to obtain a ratio of the positive electrode charge transfer impedance to the total battery impedance, which is recorded as R, and the range of R is 0.5-8%.
[0048] The present invention further studies and finds that the positive electrode charge transfer impedance ratio (R value) of the positive electrode plate has a significant effect on the energy density of the battery and the discharge power at low temperature and low SOC. Under low temperature conditions, the R value is particularly critical to the discharge power of the battery. A smaller R value means that the positive electrode material has better charge transfer ability, which helps the battery to maintain a higher discharge power at low temperatures. When the R value is too high, the transfer speed of charge between the electrodes will be limited, resulting in a significant reduction in the discharge power of the battery at low temperatures, showing poor low temperature performance. However, the R value should not be too low. In order to obtain a low R value, it is often necessary to perform specific modifications on the positive electrode active material or to perform special designs on the plate, resulting in poor lithium ion transmission and kinetic performance, resulting in the battery's discharge voltage being lowered, resulting in a lower battery energy density. When R is 0.5~8%, preferably 0.9~7.5%, the secondary battery containing the positive electrode plate can have both good discharge power and energy density at low temperature and low SOC.
[0049] The present invention does not limit the detection method of R. Those skilled in the art can detect the positive electrode charge transfer impedance ratio according to conventional methods, such as the electrochemical impedance spectroscopy (EIS) method. For example, R can be tested and obtained by the following method:
[0050] At room temperature, the secondary battery was discharged at 0.05C to 2.5V and then cut off, and the battery was charged to 80% SOC (charged to 4.25V at 0.33C constant current, charged at constant voltage until the current dropped to 0.05C, the last cycle discharge capacity was taken as the nominal capacity, and discharged to 80% SOC at 0.33C); then, the secondary battery was subjected to electrochemical impedance spectroscopy (EIS) test, and the test frequency range was 0.01Hz to 1MHz; after the test, the EIS curve was converted into a DRT curve using the DRTools data conversion tool, and the ratio of the positive electrode charge transfer impedance to the total battery impedance was calculated, which is R;
[0051] Among them, the value of the positive electrode charge transfer impedance is the peak area of the DRT curve in the range of 0.1s to 1s (the specific integration range is adjusted according to the actual measurement results), and the value of the total battery impedance is the sum of all peak areas in the DRT curve.
[0052] The R value is related to many factors, such as the element composition of the positive electrode active material, the proportion of the element content, the surface coating, etc. The R value can be controlled by adjusting the specific type of the positive electrode active material, the doping element and its content, the carbon coating layer and the coating thickness.
[0053] As a preferred embodiment of the present invention, the secondary battery satisfies the following relationship: 0.5≤(△U / Q) 0.25 ×R≤20; the unit of U is mV, the unit of Q is %, and the unit of R is %.
[0054] The present invention has found that the potential difference between the second and third discharge platforms and the capacity proportion of the third platform will affect each other with R. The change in R value indicates that the polarization of the battery is changing, which in turn affects the platform pressure difference at the battery end; the change in Q value will cause the kinetic change of the overall electrode material, which in turn affects the R value.
[0055] Taking into account the mutual influence of △U, Q and R, the present invention further finds that by comprehensively controlling △U, Q and R, the discharge power and energy density of the battery are relatively better. Among them, the 0.25 power processing of △U / Q is to achieve more reasonable data analysis and application by smoothing data changes. When (△U / Q) 0.25 When ×R is too high, the battery's discharge power may decrease at low temperatures and low SOC. 0.25 When ×R is too low, it may result in a relatively low energy density of the battery.
[0056] As a more preferred embodiment of the present invention, the secondary battery satisfies the following relationship: 1.0≤(△U / Q) 0.25 ×R≤13; the unit of U is mV, the unit of Q is %, and the unit of R is %.
[0057] When △U, Q and R further satisfy 1.0≤(△U / Q) 0.25 When ×R≤13, the discharge power and energy density of the secondary battery containing the positive electrode sheet are relatively better.
[0058] As a preferred embodiment of the present invention, the positive electrode active material includes a first active material and a second active material, the first active material includes a lithium iron manganese phosphate material, and the second active material includes a lithium iron phosphate material.
[0059] As a preferred embodiment of the present invention, the positive electrode active material includes a first active material and a second active material, the first active material and the second active material both include lithium iron manganese phosphate material, and the manganese content in the first active material is greater than the manganese content in the second active material.
[0060] The introduction of the specific third discharge platform in the present invention can be achieved by blending different types of positive electrode active materials. The positive electrode active material includes a first active material and a second active material, wherein the first active material can be a lithium iron manganese phosphate material, and the second active material can be a lithium iron phosphate material or a lithium iron manganese phosphate material having a lower manganese content than the first active material.
[0061] It should be noted that the manganese content in the present invention refers to the molar content of manganese in the material to the total content of other metal elements except lithium. For example, the manganese content of the first active material refers to the molar content of manganese in the first active material to the total content of other metal elements except lithium in the first active material.
[0062] The present invention does not limit the method for detecting the manganese content, and those skilled in the art can detect the manganese content in the positive electrode active material according to conventional technical means.
[0063] For example, the manganese content can be detected by the following method:
[0064] The battery is disassembled to obtain the positive electrode sheet, which is then processed to obtain the positive electrode active material powder. The molar content of manganese in the positive electrode active material as a percentage of the total content of other metal elements except lithium is obtained through scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS) testing, which is the manganese content.
[0065] As a preferred embodiment of the present invention, when the first active material includes lithium iron manganese phosphate material, the second active material includes lithium iron phosphate material, and the mass ratio of the first active material to the second active material is ≥1, the range of ΔU is 43~184mV.
[0066] As a further preferred embodiment of the present invention, when the first active material includes lithium iron manganese phosphate material, and the manganese content of the first active material is 50~90 mol%, the second active material includes lithium iron phosphate material, and the mass ratio of the first active material to the second active material is ≥1, the range of △U is 123~165mV.
[0067] In the case where the first active material includes a lithium iron manganese phosphate material and the second active material includes a lithium iron phosphate material, when the mass ratio of the first active material to the second active material is ≥1, that is, the proportion of the lithium iron manganese phosphate material is relatively larger, the lithium iron manganese phosphate material is dominant in the positive electrode active material, especially when the lithium iron manganese phosphate material has a high manganese content, the manganese content in the positive electrode active material is relatively high. At this time, when △U meets the above preferred range, it can avoid the second discharge platform being too high, and avoid poor low-temperature power performance caused by degradation of the battery's kinetic performance.
[0068] As a preferred embodiment of the present invention, when the first active material includes lithium iron manganese phosphate material, the second active material includes lithium iron phosphate material, and the mass ratio of the first active material to the second active material is less than 1 and greater than 0; the range of △U is 122~192mV.
[0069] When the first active material includes lithium iron manganese phosphate material and the second active material includes lithium iron phosphate material, when the proportion of lithium iron phosphate material is relatively larger, lithium iron phosphate material is dominant in the positive electrode active material. In order to ensure that the specific energy density of the battery is within an appropriate range, the preferred range of △ is 122~192mV.
[0070] As a further preferred embodiment of the present invention, when the first active material includes lithium iron manganese phosphate material, and the manganese content of the first active material is 50~90 mol%, the second active material includes lithium iron phosphate material, and the mass ratio of the first active material to the second active material is less than 1 and greater than 0, the range of △U is 137~172 mV.
[0071] As a preferred embodiment of the present invention, when the first active material and the second active material both include lithium iron manganese phosphate materials, and the manganese content in the first active material is greater than the manganese content in the second active material, and the mass ratio of the first active material to the second active material is ≥1; the range of △U is 23~144mV.
[0072] As a preferred embodiment of the present invention, when the first active material and the second active material both include lithium iron manganese phosphate materials, and the manganese element content in the first active material is greater than the manganese element content in the second active material, and the mass ratio of the first active material to the second active material is less than 1 and greater than 0; the range of △U is 44~178mV.
[0073] When the first active material and the second active material both include lithium manganese iron phosphate materials, taking into account the overall manganese content of the positive electrode active material, when ΔU is controlled within the above preferred range, the low-temperature discharge power and specific energy density of the battery are better overall.
[0074] As a preferred embodiment of the present invention, the positive electrode active material includes a core and a carbon layer arranged on the outer surface of the core, the core includes lithium iron manganese phosphate or lithium iron phosphate; the average thickness of the carbon layer is H, in nm; the particle diameter of the core is D, in nm, and the thickness-to-diameter ratio of the positive electrode active material is k=H / (D 0.7 )-0.05, and the range of k is 0.033~0.136.
[0075] The chemical structural formula of the lithium manganese iron phosphate is LiMn x Fe y M z n PO4, wherein 0<x<1, 0<y<1, 0≤z<1, and 2(x+y)+n×z=2; M is a doping element, and n is the valence state of the M element.
[0076] As a preferred embodiment of the present invention, the doping element may include at least one of vanadium (V), titanium (Ti), tungsten (W), cobalt (Co), and magnesium (Mg).
[0077] The chemical structural formula of the lithium manganese iron phosphate is LiFePO4.
[0078] In the present invention, the dynamic performance balance of the positive electrode and the negative electrode of the battery is adjusted by adjusting the relationship between H and D. 0.7 )-0.05, where H is the average thickness of the carbon layer, and D is the particle diameter of the inner core in the positive electrode active material. The present invention has found that by controlling the size of the k value, the adsorption and wetting ability of the positive electrode active material coated with the carbon layer to the electrolyte, as well as the solid phase transmission rate of lithium ions can be reflected. When the k value is low, the kinetic performance of the positive electrode is relatively weak, that is, the lithium ion transmission rate is relatively low. Conversely, when the k value is high, the thickness of the carbon layer does not match the size of the inner core particles, which will limit the transmission of lithium ions and lead to a decrease in power performance; in addition, a k value that is too large will also cause a small proportion of the material that exerts the overall capacity in the positive electrode active material, and a reduced battery energy density.
[0079] As a preferred embodiment of the present invention, the range of k is 0.076~0.129.
[0080] As a preferred embodiment of the present invention, for the positive electrode active material whose core is lithium manganese iron phosphate, the range of k is 0.056~0.136, preferably 0.078~0.129.
[0081] As a preferred embodiment of the present invention, for the positive electrode active material whose core is lithium iron phosphate, the range of k is 0.033-0.125, preferably 0.076-0.116.
[0082] As a preferred embodiment of the present invention, the average thickness (H) of the carbon layer is 4-8 nm.
[0083] As a preferred embodiment of the present invention, the average particle diameter (D) of the inner core is 80-200 nm.
[0084] In the present invention, the detection method of H and D is not limited. Those skilled in the art can detect the thickness of the carbon layer and the particle diameter of the inner core according to conventional technical means (such as TEM combined with EDS).
[0085] Exemplarily, H and D can be detected by the following method:
[0086] Take an empty positive electrode sheet and soak it in a dimethyl carbonate (DMC) solution at room temperature for 4 hours. After soaking, take out the positive electrode sheet and dry it in a vacuum environment, and use a ceramic knife to scrape the positive electrode active material powder on the surface of the positive electrode sheet;
[0087] The scraped positive electrode active material powder is evenly dispersed in ethanol and subjected to TEM (transmission electron microscope) test. In the TEM observation field, EDS (energy dispersive X-ray spectroscopy) element analysis is used to confirm that the material is lithium iron phosphate material or lithium manganese iron phosphate material;
[0088] The lithium iron phosphate or lithium iron manganese phosphate core in the positive electrode active material particles is drawn along the long and short diameter directions, the diameter is measured, and the average value is calculated to obtain the particle diameter of the core of the positive electrode active material;
[0089] Select 3 different positions on a single positive electrode active material, measure the thickness of the carbon layer coated on the outer surface of the inner core, and calculate the average value to obtain the carbon layer thickness of the positive electrode active material particle;
[0090] Repeat the above measurement steps to ensure that at least 100 particle diameters and carbon layer thicknesses of the positive electrode active material are measured, and then calculate the average value to obtain the average particle diameter (D) of the inner core and the average thickness (H) of the carbon layer.
[0091] As a preferred embodiment of the present invention, when the first active material and the second active material both include lithium iron manganese phosphate materials, the difference between the manganese content in the first active material and the manganese content in the second active material is 20-80%.
[0092] In the present invention, the preparation method of the lithium iron manganese phosphate material is not limited, and those skilled in the art can prepare the lithium iron manganese phosphate material according to conventional technical means.
[0093] Exemplarily, the preparation method of lithium manganese iron phosphate material may include the following steps:
[0094] Mixing a manganese source, an iron source, a phosphorus source, a lithium source and a carbon source (if any) in a certain molar ratio and ball milling;
[0095] The ball-milled product is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0096] The sintered material is crushed and screened to obtain lithium manganese iron phosphate material.
[0097] Exemplarily, the method for preparing lithium manganese iron phosphate material may further include the following steps:
[0098] The lithium manganese iron phosphate precursor (Mn a Fe b PO4 precursor, a+b=1) is mixed with a lithium source and ball-milled, and then a phosphorus source is added to adjust the Li / P ratio of the reactants. If necessary, a carbon source is also added, and the mixture is ball-milled together;
[0099] The ball-milled product is sintered in an atmosphere with an oxygen concentration of less than 150 ppm;
[0100] The sintered material is crushed and screened to obtain lithium manganese iron phosphate material.
[0101] The preparation method of lithium iron phosphate material is similar to that of lithium iron manganese phosphate material, the difference is that no manganese source is added, or FePO4 precursor is used.
[0102] The lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0103] The phosphorus source may include at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, or lithium phosphate.
[0104] The iron source may include at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferric acetate, ferrous acetate, ferric carbonate, ferrous carbonate, ferrous oxide, ferrous oxide or ferric oxalate.
[0105] The manganese source may include at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, or manganese acetate.
[0106] The carbon source may include glucose and / or sucrose.
[0107] Ferromanganese phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; ferric phosphate can be selected as a manganese source, an iron source and a phosphorus source at the same time; the lithium source can include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.
[0108] When preparing lithium iron manganese phosphate material and / or lithium iron phosphate material, a certain amount of doping element source such as vanadium source (vanadium pentoxide), tungsten source (ammonium metatungstate), titanium source (titanium oxide), magnesium source (magnesium carbonate), etc. can be mixed with manganese source (if any), iron source, phosphorus source, lithium source as needed to obtain lithium iron manganese phosphate material and / or lithium iron phosphate material containing a certain amount of doping elements.
[0109] Optionally, the solvent may be at least one of water and ethanol.
[0110] Alternatively, the milling may be ball milling.
[0111] By adjusting the addition amount of manganese source, iron source and phosphoric acid, the proportion of manganese content in lithium manganese iron phosphate material can be controlled.
[0112] The thickness of the coated carbon layer can be controlled by adjusting the amount of carbon source added and the ball milling conditions.
[0113] The conductive agent can be used as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. In the present invention, there is no particular limitation on the type of the conductive agent. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black or graphene.
[0114] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the conductive agent can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0115] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0116] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art, for example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0117] In addition to the positive electrode plate, the secondary battery also includes a negative electrode plate, a separator and an electrolyte.
[0118] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. For the negative electrode active material, the embodiment of the present invention does not specifically limit the type of the negative electrode active material, and can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, and silicon-carbon composites.
[0119] The diaphragm is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.
[0120] The electrolyte of the present invention can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.
[0121] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5-5 mol / L.
[0122] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0123] Electrical devices
[0124] An embodiment of the present invention provides an electric device, comprising the secondary battery described above.
[0125] The electrical device serves as a power supply for the electrical device.
[0126] The electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other energy forms, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0127] The present invention is further described below with reference to specific embodiments.
[0128] Example 1
[0129] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:
[0130] (1) Preparation of positive electrode
[0131] (1.1) Preparation of positive electrode active materials
[0132] Preparation of the first positive electrode active material:
[0133] According to LiMn x Fe 1-x Lithium carbonate, manganese carbonate, ferrous oxalate and diammonium hydrogen phosphate are weighed and mixed in molar proportions of the elements Li, Mn, Fe and P in the PO4 chemical formula, wherein the value of x is 0.68, to obtain a mixture;
[0134] Based on the total weight of the manganese source (manganese carbonate) and the iron source (ferrous oxalate), the doping element source (the doping element is vanadium, and the doping element source is vanadium pentoxide) is weighed according to a doping amount of 1000 ppm by mass;
[0135] The mixed material and part of the doping element source (50 wt.% of the doping element source) were ball-milled together at a ball-milling speed of 500 rpm. After ball-milling for 1 hour, the remaining doping element source (the remaining 50 wt.% of the doping element source) was added and the ball-milling was continued for a total of 8 hours.
[0136] The ball-milled product was placed in a tubular furnace and sintered in a nitrogen atmosphere at a constant temperature of 700° C. for 10 hours. After cooling to room temperature, lithium manganese iron phosphate material was obtained, which was the first positive electrode active material.
[0137] Preparation of the second positive electrode active material:
[0138] The precursor (FePO4 precursor prepared by solvent method) was mixed with LiOH in a molar ratio of 1:1. The average diameter of the precursor is shown in Table 1. The mixture was ball-milled for 3 h at 350 rpm, and then NH4H2PO4 was added to adjust the Li / P ratio of the reactants, and a carbon source (glucose); the amount of carbon source added (the mass ratio of carbon source to the total amount of precursor, LiOH and NH4H2PO4) was 5.3 wt.%; and the mixture was ball-milled for 2 h at 500 rpm.
[0139] The ball-milled product was placed in a tube furnace and sintered in a nitrogen atmosphere. The sintering conditions were as follows: from 25°C, the temperature was raised to 700°C at a heating rate of 5°C / min. When the sintering temperature was raised to 300°C and 600°C, the temperature was kept constant for 1 h.
[0140] After cooling to room temperature, a lithium iron phosphate material having a lithium iron phosphate (LiFePO4) core and a carbon layer on the outer surface of the core is obtained, which is the second active material.
[0141] (1.2) The first positive electrode active material and the second positive electrode active material are mixed uniformly in a mass ratio of 25:75 to obtain a positive electrode active material;
[0142] The positive electrode active material, binder (PVDF), conductive agent SP, and conductive agent CNT are mixed evenly in NMP at a mass ratio of 97:1.5:1:0.5. Subsequently, the mixed positive electrode slurry is evenly coated on aluminum foil and dried in a vacuum oven at 100°C to obtain a positive electrode sheet, which is then cut into strips and then rolled to obtain a positive electrode sheet.
[0143] (2) Preparation of negative electrode sheet
[0144] The negative electrode active material (artificial graphite), conductive agent (SP), and binder (carboxymethyl cellulose, CMC) are mixed in a mass ratio of 96.4:1:2.6, dispersed in deionized water, and made into negative electrode slurry by a wet process using a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven at 100°C for drying for 12 hours, and then rolled and cut to obtain negative electrode sheets.
[0145] (3) Preparation of electrolyte
[0146] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a weight ratio of 3:7 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1.15 mol / L.
[0147] (4) Preparation of diaphragm
[0148] Polyethylene (PE) diaphragm is used.
[0149] (5) Preparation of batteries
[0150] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0151] Examples 2 to 25 and Comparative Examples 1 to 8
[0152] Examples 2 to 25 and Comparative Examples 1 to 8 provide a lithium ion battery, respectively, and the preparation method is basically the same as that of Example 1, except that:
[0153] The manganese content (value of x) in the first active material is shown in Table 1;
[0154] The type and doping amount of the doping element in the first active material are shown in Table 1. The first active materials of some embodiments and comparative examples have no doping element, which is marked as “ / ” in Table 1;
[0155] For the embodiments and comparative examples in which the first active material contains a doping element, the ball milling speed and the total ball milling time remain unchanged, and other ball milling conditions are shown in Table 1;
[0156] The type of the second active material (lithium manganese iron phosphate material is recorded as LMFP, and lithium iron phosphate material is recorded as LFP) is shown in Table 1; when the type of the second active material is LMFP, the precursor is selected as Mn y Fe 1-y For PO4 precursor, the values of y are shown in Table 1;
[0157] The average diameter of the precursor in preparing the second active material is shown in Table 1; the amount of carbon source added is shown in Table 1;
[0158] In the sintering conditions of the second active material, the heating rate and the sintering temperature are shown in Table 1;
[0159] The mass ratio of the first active material to the second active material is shown in Table 1.
[0160] Table 1
[0161]
[0162] When the second active material is a lithium iron phosphate material, the D and H in the lithium iron phosphate materials prepared in each embodiment and comparative example are detected, and the detection method is as follows:
[0163] Take the positive electrode sheet of the lithium-ion battery in an empty state, soak it in a dimethyl carbonate (DMC) solution at room temperature for 4 hours, take out the positive electrode sheet after soaking and dry it in a vacuum environment, and scrape the positive active material powder on the surface of the positive electrode sheet with a ceramic knife;
[0164] The scraped positive electrode active material powder is evenly dispersed in ethanol and subjected to TEM (transmission electron microscope) test. In the TEM observation field, EDS (energy dispersive X-ray spectroscopy) element analysis is used to confirm that the material is lithium iron phosphate material or lithium manganese iron phosphate material;
[0165] The lithium iron phosphate or lithium iron manganese phosphate core in the positive electrode active material particles is drawn along the long and short diameter directions, the diameter is measured, and the average value is calculated to obtain the particle diameter of the core of the positive electrode active material;
[0166] Select 3 different positions on a single positive electrode active material, measure the thickness of the carbon layer coated on the outer surface of the inner core, and calculate the average value to obtain the carbon layer thickness of the positive electrode active material particle;
[0167] Repeat the above measurement steps to ensure that at least 100 particles of the positive electrode active material are measured in terms of particle diameter and carbon layer thickness, and then calculate the average value to obtain the average particle diameter (D) of the core and the average thickness (H) of the carbon layer;
[0168] Calculate k based on D and H, k = H / (D 0.7 )-0.05.
[0169] The △U and Q of lithium-ion batteries are tested as follows:
[0170] (1) Constant capacity: The lithium-ion battery was left at rest for 120 min at 25°C, and discharged at a constant current of 0.33C to 2.5V; after resting for 20 min, it was charged at a constant current and constant voltage of 0.33C to a cut-off voltage of 4.25V and a cut-off current of 0.05C; after resting for 20 min, it was discharged at a constant current of 0.33C to 2.5V; after repeating the above steps once, the discharge QV data and discharge VQ data of the second cycle were obtained;
[0171] (2) Drawing a dQ / dV-V curve: Based on the above discharge QV data, 100 points are sampled at equal intervals as the initial data of Dv and Dq, and the voltage and power data of the nth data point are subtracted from the voltage and power data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dQ is divided by dV to obtain dQ / dV; dQ / dV is used as the ordinate and voltage is used as the abscissa to draw a dQ / dV-V curve;
[0172] (3) In the obtained △U:dQ / dV-V curve, in the range of 3.0~4.1V, according to the order of the horizontal axis voltage from low to high, the horizontal axis voltage U3 corresponding to the peak position of the first characteristic peak is the potential of the third discharge platform, the horizontal axis voltage U2 corresponding to the peak position of the second characteristic peak is the potential of the second discharge platform, and the horizontal axis voltage U1 corresponding to the peak position of the third characteristic peak is the potential of the first discharge platform;
[0173] U2-U3=potential difference between the second discharge platform and the third discharge platform (△U);
[0174] (4) Drawing a dV / dQ-Q curve: Based on the above discharge VQ data, 100 points are sampled at equal intervals as the initial data of Dv and Dq, and the voltage and power data of the nth data point are subtracted from the voltage and power data of the n+1th data point to obtain a dV and dQ data; all the data are processed in sequence to obtain a series of dV and dQ data; then dV is divided by dQ to obtain dV / dQ; dV / dQ is used as the ordinate and Q is used as the abscissa to draw a dV / dQ-Q curve;
[0175] (5) Obtaining Q: In the dV / dQ-Q curve, the maximum horizontal axis is the total discharge capacity Q0, and the peak close to the Q0 side (right side) is defined as peak C; the horizontal axis capacity corresponding to the peak value of the total discharge capacity-peak C is the discharge capacity of the third discharge platform (denoted as Q3). The proportion of the discharge capacity of the third discharge platform to the total discharge capacity (Q) = Q3 / Q0×100%.
[0176] The R of the positive electrode is tested as follows:
[0177] At room temperature, the lithium-ion battery was discharged at 0.05C to 2.5V and then cut off, and the battery was charged to 80% SOC. Subsequently, the lithium-ion battery was subjected to an electrochemical impedance spectroscopy (EIS) test with a test frequency range of 0.01Hz to 1MHz. After the test, the EIS curve was converted into a DRT curve using the DRTools data conversion tool, and the ratio of the positive electrode charge transfer impedance to the total battery impedance, i.e. R, was calculated.
[0178] Among them, the value of the positive electrode charge transfer impedance is the peak area of the DRT curve in the range of 0.1s to 1s, and the value of the total battery impedance is the sum of all peak areas in the DRT curve of the positive and negative electrodes.
[0179] The test results are shown in Table 2.
[0180] Table 2
[0181]
[0182] The performance test of the low temperature and low SOC discharge power performance and energy density of lithium-ion batteries is carried out as follows:
[0183] (1) Discharge power performance at low temperature and low SOC:
[0184] The lithium-ion battery was charged to 4.25V at room temperature with a constant current of 0.33C, and then charged at a constant voltage until the current dropped to 0.05C. After standing for 5 minutes, the battery was discharged to 2.5V at a constant current of 0.33C. This was one cycle. After two cycles, the discharge capacity of the second week was used as the standard capacity and the charge was adjusted to 5% SOC.
[0185] The lithium-ion battery is placed at -20°C, left to stand for 2 hours for temperature equilibrium, and then discharged with a 0.7C pulse for 180 seconds, with a signal acquisition frequency of 100ms. The value of the last voltage acquisition point is tested and is the discharge termination voltage value. The present invention uses the discharge termination voltage value of the battery at -20°C and 5% SOC with a 0.7C pulse discharge for 180 seconds to reflect the discharge power performance at low temperature and low SOC. The discharge termination voltage is determined by the initial voltage and the voltage drop. When the current is consistent, the size of the discharge termination voltage directly determines the level of the discharge power. Therefore, in each embodiment and comparative example of the present invention, the larger the discharge termination voltage, the better the low temperature and low SOC discharge power performance of the battery.
[0186] (2) Energy density performance:
[0187] The lithium-ion battery is charged to 4.25V at 0.33C constant current at 25°C, and then charged at constant voltage until the current drops to 0.05C. After standing for 5 minutes, the battery is discharged to 2.5V at 0.33C constant current. This is one cycle. After two cycles, the discharge capacity of the second week is recorded and divided by the mass of the positive electrode active material (when preparing the pole piece, weigh the mass of the pole piece minus the mass of the current collector and multiply it by the mass proportion of the positive electrode active material in the positive electrode slurry) to calculate the gram capacity (in MAh / g). At the same time, the average discharge voltage (in V) of the second week is recorded, and the gram capacity is multiplied by the average voltage to calculate the 25°C specific energy density (in WH / kg). The present invention reflects the energy density performance of the battery with the 25°C specific energy density.
[0188] Figure 1 : is a discharge curve diagram of the lithium ion battery of Example 7. It can be seen that the discharge curve includes three discharge platforms with different potentials, which are recorded as the first discharge platform, the second discharge platform and the third discharge platform in descending order of potential.
[0189] Figure 2 This is the dQ / dV-V curve of the lithium-ion battery of Example 7. According to the order of the horizontal axis voltage from low to high, the horizontal axis voltage U3 corresponding to the peak position of the first characteristic peak is the potential of the third discharge platform, the horizontal axis voltage U2 corresponding to the peak position of the second characteristic peak is the potential of the second discharge platform, and the horizontal axis voltage U1 corresponding to the peak position of the third characteristic peak is the potential of the first discharge platform; △U=U2-U3=165mV.
[0190] Figure 3 dV / dQ-Q curve of the lithium ion battery of Example 7, the discharge capacity of the third discharge platform accounts for 8.3% of the total discharge capacity.
[0191] The test results are shown in Table 3.
[0192] Table 3
[0193]
[0194] According to the test results in Table 3, it can be seen that the lithium-ion batteries prepared in various embodiments of the present invention have good low-temperature, low SOC discharge power performance and high energy density, and the discharge termination voltage value of 180s with 0.7C pulse discharge at -20°C and 5% SOC is ≥1.212V, and the specific energy density at 25°C is ≥437 WH / kg. In Comparative Examples 1 to 7, when △U or Q exceeds the range of the technical solution of the present invention, it is difficult for the lithium-ion battery to have both qualified discharge power performance and energy density.
[0195] It can be seen from Examples 13 to 16 that when the value of R is within the preferred range of 0.5 to 8%, especially within the preferred range of 0.9 to 7.5%, the combined effects of the discharge performance and energy density of the battery are better.
[0196] It can be seen from Examples 17 to 19 that when the lithium-ion battery further satisfies 1.0≤(△U / Q) 0.25 When ×R≤13, the battery's low temperature, low SOC discharge performance and energy density are relatively more balanced.
[0197] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, characterized in that: The positive electrode active material includes a lithium-containing material with an olivine structure; The positive electrode active material includes a first active material and a second active material, the first active material includes a lithium iron manganese phosphate material, and the second active material includes lithium iron phosphate or lithium iron manganese phosphate coated with a carbon layer; When the second active material includes lithium manganese iron phosphate, the molar percentage of manganese in the first active material to the metal elements other than lithium is greater than the molar percentage of manganese in the second active material to the metal elements other than lithium; The secondary battery is charged and discharged at 25°C and 0.33C in a voltage range of 2.5-4.25V to obtain a discharge curve; the discharge curve includes three discharge platforms with different potentials, which are sequentially recorded as the first discharge platform, the second discharge platform and the third discharge platform in order from high to low potential; The potential difference between the second discharge platform and the third discharge platform is recorded as △U, and the range of △U is 23~192mV; The proportion of the discharge capacity of the third discharge platform to the total discharge capacity of the secondary battery is recorded as Q, and the range of Q is 3.5~88%.
2. The secondary battery according to claim 1, characterized in that: The range of △U is 50~175mV.
3. The secondary battery according to claim 1, characterized in that: The range of Q is 8.0~82%.
4. The secondary battery according to claim 1, characterized in that: The secondary battery is subjected to EIS test, and the ratio of the positive electrode charge transfer impedance to the total battery impedance is recorded as R, and the range of R is 0.5~8%.
5. The secondary battery according to claim 4, characterized in that: The secondary battery satisfies the following relationship: 0.5≤(△U / Q) 0.25 ×R≤20; the unit of △U is mV, the unit of Q is %, and the unit of R is %.
6. The secondary battery according to claim 5, characterized in that: The secondary battery satisfies the following relationship: 1.0≤(△U / Q) 0.25 ×R≤13.
7. The secondary battery according to claim 1, characterized in that: The positive electrode active material comprises a core and a carbon layer disposed on the outer surface of the core, wherein the core comprises lithium manganese iron phosphate or lithium iron phosphate; The average thickness of the carbon layer is H, and the unit of H is nm; the particle diameter of the core is D, and the unit of D is nm; the thickness-to-diameter ratio of the positive electrode active material is k=H / (D 0.7 )-0.05, and the range of k is 0.033~0.
136.
8. The secondary battery according to claim 7, characterized in that: The range of k is 0.076~0.
129.
9. The secondary battery according to claim 7, characterized in that: The average thickness of the carbon layer is 4-8 nm, and / or the particle diameter of the inner core is 80-200 nm.
10. The secondary battery according to claim 1, characterized in that: The difference between the molar percentage of manganese in the first active material to the metal elements other than lithium and the molar percentage of manganese in the second active material to the metal elements other than lithium is 20-80 mol %.
11. The secondary battery according to claim 1 or 2, characterized in that: The potential of the second discharge platform is 3.25-3.4 V, and / or the potential of the third discharge platform is 3.1-3.25 V.
12. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 11.
Citation Information
Patent Citations
LiMnPO4 / C lithium ion battery anode material prepared by template method and preparation method of anode material
CN103441282A
Lithium manganese iron phosphate composite electrode plate as well as preparation method and application thereof
CN116759540A